2018
DOI: 10.1002/ejlt.201800251
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐Catalyzed Butanolysis of Echium Oil for the Selective Enrichment in Gamma‐Linolenic and Stearidonic Acids

Abstract: Enzymatic butanolysis of Echium oil in the presence of lipases from Candida rugosa and Rhizopus oryzae has been studied. The effects of lipase immobilization, hydration of the reaction mixture and oil oxidation degree on lipase catalytic activity, fatty acid selectivity, and inactivation degree are evaluated. The utilization of butanol containing 2.5% (w/w) of water produces the highest catalytic activity of lipases in both powder and immobilized form; particularly of immobilized lipase from Rhizopus oryzae, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Karabulut et al [58] investigated the selectivity of three lipases for C18 unsaturated fatty acids in catalyzing acidolysis and found that Lipozyme TL IM, Lipozyme RM IM and Novozym 435 all had the fatty acid substrate preference in the order of C18:3 > C18:2 > C18:1. On the contrary, Corzo-Martínez et al [78] found that immobilized lipase from Rhizopus oryzae showed preference for C18 with lower unsaturated degree.…”
Section: Substrate Specificity Of Lipasementioning
confidence: 95%
“…Karabulut et al [58] investigated the selectivity of three lipases for C18 unsaturated fatty acids in catalyzing acidolysis and found that Lipozyme TL IM, Lipozyme RM IM and Novozym 435 all had the fatty acid substrate preference in the order of C18:3 > C18:2 > C18:1. On the contrary, Corzo-Martínez et al [78] found that immobilized lipase from Rhizopus oryzae showed preference for C18 with lower unsaturated degree.…”
Section: Substrate Specificity Of Lipasementioning
confidence: 95%